Challenge of Bauxite Logistics - Lee, Sue Yee; Sorooshian, Shahryar; Maarof, Mohd Ghazali; Muzamir, Hasan (Oklahoma State University, 2018)
Bauxite industry has growth rapidly. This global sourcing or world cargo has increased the risks toward the bauxite industry especially in the transportation of the bauxite mining. The associated risks include of the loss of high profit bauxite through transportation, the destructive of the environment, compensation toward the communities and forth. Therefore, this note highlights that a security management system is typically required to secure the logistics and supply chain from the risk and reduce the impact on the communities and environment.